(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2018)
Experience has shown that the attitude of the person assuming the management functions in the school is a key and decisive element in the quality of the change processes in the school. Of these ideas is born, the concept of (DL). METHOD. The research design as a qualitative study by a case study. The main objective is to understand the four dimensions of DL and the actions of the Principal through representative cases of two public schools. The techniques used to collect information were documentary analysis, questionnaires, in-depth structured interviews, and observation. RESULTS AND DISCUSSION. The results found are very broad and correspond to the two schools. This research presents the results of the LD, which refers to the responses given by two Principals, of the four dimensions (DL Practices, Shared Decisions, Mission, Vision and Professional Development). The conclusions are extensive and will be explained in the development of communication. Key-words: Dimensions of distributed leadership; Case study; Distributed leadership; Spanish schools, Principals.